RANCANGAN STRATEGI KEPEMIMPINAN KEPALA DESA DI DESA MAJASARI - Somadi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim : This research aims to determine the obstacles to implementing village head leadership and village head leadership strategies in Majasari Village. Design/Methode/Approach : This research uses a qualitative approach with data analysis techniques, namely SWOT analysis. Research Finding : The obstacles faced in implementing village head leadership in Majasari Village are administrative obstacles. The village head's leadership strategy in Majasari Village is an aggressive strategy. Practitionel/Policy implication : The leadership strategy implemented by the village head in Majasari Village is an aggressive strategy. Research limitation : The research focuses on the leadership of the village head in Majasari Village.